Characterization, quantification, and behavior of neoplastic monoclonal gammopathies in dogs and cats - Jeffries, Christina Michelle, author; Moore, A. Russell, advisor; Avery, Paul, advisor; Rao, Sangeeta, committee member; Vickery, Kate, committee member (Colorado State University. Libraries, 2022)
Monoclonal immunoglobulin (M-protein) production can occur in a number of myeloma related diseases (MRD) in domestic animals, including multiple myeloma (MM), extramedullary plasmacytomas, solitary osseous plasmacytoma, IgM Waldenstroms macroglobulinemia/lymphoplasmacytic lymphoma, immunoglobulin secreting lymphomas and leukemias, and plasma cell leukemia. This thesis seeks to improve upon the current knowledge of MRDs by examining diagnostic methods, possible biases (such as hyperproteinemia), and by describing a large population of dogs and cats with confirmed M-proteins. Differentiation of polyclonal and monoclonal gammopathies can be achieved by serum protein electrophoresis (SPE) and immunofixation (IF). Agarose gel electrophoresis (AGE) is the most commonly used SPE method within veterinary medicine and a previous study validated a method for AGE SPE densitometric M-protein (dM-protein) quantification. Capillary zone electrophoresis (CZE) is another method of SPE that can be performed more rapidly than AGE SPE that may have increased sensitivity with similar specificity. We sought to compare these two methods of SPE to determine if CZE SPE is a comparable alternative method for dM-protein quantification in dogs and cats. We found that these methods performed similarly, and both appear to be acceptable methods for dM-protein quantification, but they should not be used interchangeably. This finding indicates that the previously published method for dM-protein quantification can also be used with CZE SPE in dogs and cats. Hyperglobulinemia, hyperproteinemia, and hypoalbuminemia are frequently used criteria to prompt SPE in dogs and cats, but M-protein production can occur in humans and animals without these criteria being met. The assumption that these criteria need to be present to raise concern for M-protein production may lead to delayed diagnosis in patients that have early MRD or low concentration M-protein production. Retrospective evaluation of samples submitted to our lab for SPE and IF between January 2014 and December 2019 identified 18 cases of confirmed M-proteins in dogs with normal total protein concentrations. Most of these animals had confirmed, or suspected, myeloma related disease or lymphoproliferative disorders which prompted SPE. A subset of these cases were evaluated to highlight the diagnostic utility of IF in cases with low concentration M-proteins. In all 7 cases evaluated, IF was needed to make a definitive diagnosis of an M-protein. Based on these findings, we recommend running SPE and IF in tandem to increase diagnostic accuracy for M-protein detection. Large studies characterizing dogs with monoclonal immunoglobulins are rare within the literature, with the largest study by Matus et al from 1984 describing 60 dogs with MM. We sought to retrospectively evaluate a large population of dogs with SPE and IF confirmed M-proteins to add to the available literature, evaluate previously published MM prognostic indicators, assess for novel prognostic indicators, and evaluate other clinicopathology and clinical variables. 113 canine cases were included in our analysis with a total of 75 cases having complete medical records available for analysis. MM was the most common diagnosis within our population, with fewer cases falling under the spectrum of MRD. The mean age of animals diagnosed with an M-protein was 9.9 years. Treatment of MM with prednisone and melphalan led to statistically longer MSTs in these cases when compared to single agent therapy with prednisone or melphalan. Clinical signs were frequently non-specific, but some cases presented with clinical signs that are potentially more specific for MRD such as collapse, evidence of bleeding diathesis, and musculoskeletal pain. Ancillary diagnostic testing such as PCR for antigen receptor rearrangement (PARR), flow cytometry, and/or immunohistochemistry/immunocytochemistry was required in some cases to fully categorize disease. Adoption of visceral organ involvement as a primary or alternative diagnostic criterion for MM may be more likely to appropriately categorize animals with MM, at least based on the clinical course of disease. Animals within our population also frequently had total hypercalcemia, proteinuria, and occasionally had renal dysfunction. Frequently used negative prognostic indicators failed to demonstrate statistical significance (except for renal disease), but occasionally appeared to have clinically significant impacts on survival time. Similar to dogs, the available literature for cats with monoclonal immunoglobulins is sparse. The largest two studies in cats are Mellor et al and Patel et al, with 24 cats with MRD and 16 cats with MM, respectively. Again, we sought to add to the available data on cats with SPE/IF confirmed M-proteins by looking at the same criteria that were evaluated in dogs. Overall, cats with MRDs had a poorer prognosis when compared to dogs, with the exception of B cell chronic lymphocytic leukemia/lymphoma (BCLL) cases. Evidence of bleeding diathesis was not observed in our cat population and the presence of lytic bone lesions was uncommon. Hypocholesterolemia was a negative prognostic indicator for cats with MRDs (excluding BCLL, which was not included in these analyses). The validity of renal azotemia, hypercalcemia, proteinuria, and BJP as prognostic indicators could not be fully assessed in this study, due to a number of factors. Lastly, the addition of visceral organ involvement to the current veterinary MM diagnostic scheme may be warranted and can make categorization of MRDs and diagnosis of MM easier, while still correlating with the clinical behavior of these diseases in cats. The work within this thesis adds to available knowledge of MRD in dogs and cats. We have shown that the lack of hyperproteinemia does not rule out the possibility of an M-protein, especially in cases with suspected MRD. Additionally, running SPE and IF in tandem can capture cases with M-protein production that may be missed with SPE alone. CZE SPE is an acceptable alternative method for dM-protein quantification and can be used when AGE SPE is not available. Finally, we present the largest retrospective analysis of dogs and cats with confirmed monoclonal immunoglobulins to date. Similar to previous works, we found that the course of disease is more aggressive in cats with MM when compared to MM in dogs. Renal disease in dogs and hypocholesterolemia in cats were found to be negative prognostic indicators in our study, but other negative prognostic factors either failed to reach statistical significance or could not be evaluated. We strongly recommend the consideration of visceral organ involvement as an additional or alternative criterion for the diagnosis of MM in dogs and cats, as animals diagnosed with MM with this scheme had disease courses similar to those diagnosed with the current scheme. Further work should examine the frequency of BJP, proteinuria, bone involvement in MM cases without apparent musculoskeletal clinical signs.
Keywords: dogs; monoclonal immunoglobulin; myeloma related disease; monoclonal gammopathy; cats; multiple myeloma